Basic oxygen furnace and ground granulated blast furnace slag based alkali-activated pastes: Characterization and optimization - Kabay, Nihat; Miyan, Nausad; Ozkan, Hakan (ELSEVIER SCI LTD, 2021)
The steel production shows tremendous increase all over the world and the enormous production of steel has subsequently led to huge amount of basic oxygen furnace (BOF) slag generation which causes several environmental issues. Previous studies generally considered the use of BOF slag as aggregate, cement replacement material, and binder in combination with metakaolin, fly ash, gold mine tailings, and ferronickel slag in alkaliactivated systems. Apart from these, the present study proposes alkali-activation of BOF slag in replacement with ground granulated blast furnace slag (GGBFS) using sodium hydroxide (NaOH) as the activator. The fresh-state, mechanical, and microstructural properties of the alkali-activated paste samples were analyzed on 24 mixes. Test results showed that BOF slag ratio and the NaOH concentration modified the workability and the setting time, and their effect was remarkable for 6 M of NaOH and BOF content beyond 20%. The alkali-activated pastes containing 20 and 40% of BOF slag had comparable strength, however the strength reduced significantly upon further BOF slag inclusion. The increment of Ca(OH)2 with increased BOF slag ratio revealed by thermogravimetric analysis denotes its less consumption in the formation of C-S-H and support the decreasing compressive strength at 28 days. The X-Ray diffraction analysis revealed phases such as C-S-H and hydrotalcite due to hydration reactions. The scanning electron microscopy analysis showed that the microstructure was altered with BOF slag incorporation, and the micro-cracks were lowered compared to the reference. The optimization study showed that 25.5% of BOF slag and 6 M of NaOH provided higher compressive strength within the analyzed range, which was experimentally verified. Alkali-activation of BOF slag blended with GGBFS can be an efficient way of utilizing BOF slag to reduce its environmental impacts.
Keywords: Basic oxygen furnace slag; Ground granulated blast furnace slag; Alkali-activated paste; Compressive strength; Microstructure; Optimization; FLY-ASH; MECHANICAL-PROPERTIES; BLENDED CEMENTS; PERFORMANCE; HYDRATION; STRENGTH; BEHAVIOR; GEOPOLYMERS; TEMPERATURE; SHRINKAGE; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology